The ELISe experiment, potential paths towards its realization. (26th November 2015) - Simon, H
Abstract: In this paper the opportunities and prerequisites for carrying out electron scattering experiments off unstable beams for the first time will be outlined. A colliding beam experiment with intersecting electron and RIBs will be described, which allows making the best uses of the precious unstable nuclei for elastic and inelastic scattering using a pure electromagnetic probe. The experiment could be already realized within the modularized start version of the FAIR facility which is currently being constructed.